Expanding media histories Cultural and material perspectives - Bechmann Pedersen, Sune; Cronqvist, Marie; Holgersson, Ulrika (Kriterium, 2023)
Contemporary media history is a rapidly growing field that extends far beyond traditional studies of technology or institutions such as radio, film, and television. This volume expands the scope further still to analyse ephemeral, mundane phenomena long overlooked by media historiography. In eight original essays, the volume demonstrates the strengths of a broad concept of the media. The first part centres on media systems and media events, with studies of spiritist séances, Gallup polls, the mediated persona of Kaiser Wilhelm II, and the burial of a Swedish statesman in 1915. The second part focuses on media materialities and infrastructure such as art replicas, ring binders, tourist guidebooks, and media technology in the IKEA home. Aimed at students and academics alike, Expanding Media Histories offers new empirical research, which engages critically with key concepts in media history today.